2013
DOI: 10.1007/s11904-013-0183-7
|View full text |Cite
|
Sign up to set email alerts
|

Case Management Interventions for HIV-Infected Individuals

Abstract: Engagement of HIV-positive persons into care and achieving optimal antiretroviral treatment outcomes is a fundamental HIV prevention strategy. Case management model was recommended as a beneficial model of care for patients with a new HIV diagnosis, focusing on individuals with unmet needs, and linking them with the coordinated health and social services to achieve desired outcomes. HIV case management is population-driven and programs are designed to respond to the unique needs of the client population they s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
10
0
4
Order By: Relevance
“…Positive prevention has three complementary objectives in HIV-infected individuals: (1) reducing high risk sexual behaviors; (2) reducing injection and non-injection drug and alcohol abuse, where relevant; and (3) optimizing clinical care [5]. The last objective seeks to: (i) foster linkage and retention of HIV-infected persons to good care; (ii) enhance coverage and adherence to antiretroviral therapy (ART); (iii) increase full suppression of HIV viral load; and (iv) prevent development of HIV drug resistance [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Positive prevention has three complementary objectives in HIV-infected individuals: (1) reducing high risk sexual behaviors; (2) reducing injection and non-injection drug and alcohol abuse, where relevant; and (3) optimizing clinical care [5]. The last objective seeks to: (i) foster linkage and retention of HIV-infected persons to good care; (ii) enhance coverage and adherence to antiretroviral therapy (ART); (iii) increase full suppression of HIV viral load; and (iv) prevent development of HIV drug resistance [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite evidence of increased rates of HIV-related complications after release from prison, many studies have identified effective mechanisms for health maintenance, including case management, 41 discharge planning, 10 transitional care coordination, 42 and focusing on combined medical and social needs. 43 Findings from a single randomised trial did not find a benefit in the use of case management for released prisoners with HIV; however, these findings may be unique to the particular setting.…”
Section: Hiv In Prisonsmentioning
confidence: 99%
“…1 Case management (CM) has been shown to facilitate entry and engagement in care among persons living with HIV. 2,3 In the United States, HIV CM is a federally legislated program funded by the Ryan White Comprehensive AIDS Resources Emergency (CARE) Act of 1990 (now the Ryan White Treatment Modernization Act). Japan, Brazil, and Rwanda have also initiated a integrated case management program by the government.…”
mentioning
confidence: 99%
“…Japan, Brazil, and Rwanda have also initiated a integrated case management program by the government. 3 HIV-infected patients in Taiwan have been provided with free antiretroviral therapy and medical care at AIDS-designated hospitals since the early 1990s. An estimated 70% of individuals living with HIV infection in Taiwan have sought HIV care, and 40% of individuals who have sought HIV care received HAART after the diagnosis of HIV infection with CD4 cell counts < 350 cells/mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation